1996
DOI: 10.1046/j.1365-2141.1996.d01-1729.x
|View full text |Cite
|
Sign up to set email alerts
|

The reduction of large von Willebrand factor multimers in plasma in essential thrombocythaemia is related to the platelet count

Abstract: We have investigated the relationship between platelet count and large VWF (von Willebrand factor) multimers in the plasma of 36 patients with essential thrombocythaemia (ET) and 26 patients with reactive thrombocytosis (RT). In both ET and RT patients an inverse relationship could be established between platelet count and large VWF multimers in plasma as well in relatively decreased ristocetin cofactor/von Willebrand factor antigen and collagen binding activity/von Willebrand factor antigen ratios. A normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 10 publications
7
93
0
2
Order By: Relevance
“…In a previous study we showed that plasma vWF:CBA/ vWF:Ag ratios are tightly correlated to the percentage of plasma large vWF multimers [16]. The ristocetin cofactor activity, which is usually used to test vWF function in vitro, appeared to be a less sensitive parameter for detecting modest reductions of large vWF multimers in plasma, consistent with previous observations [7,14,16].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In a previous study we showed that plasma vWF:CBA/ vWF:Ag ratios are tightly correlated to the percentage of plasma large vWF multimers [16]. The ristocetin cofactor activity, which is usually used to test vWF function in vitro, appeared to be a less sensitive parameter for detecting modest reductions of large vWF multimers in plasma, consistent with previous observations [7,14,16].…”
Section: Discussionsupporting
confidence: 72%
“…Plasma vWF:Ag and vWF:CBA levels were significantly higher in RT patients as compared with both ET patients (p~0.05) and normal individuals (p~0.05). In contrast, per-centages of plasma large vWF multimers were higher in normal individuals as compared with both RT patients (p~0.01) and ET patients (p~0.01), consistent with previous observations [4,16]. There were no significant differences in pre-ASA values of Ivy BT, plasma vWF:RCoF, plasma vWF:RCoF/vWF:Ag ratio, plasma vWF:CBA/vWF:Ag ratio, MDA-AA, platelet vWF:Ag and vWF:CBA (data not shown) between ET and RT patients and normal subjects.…”
Section: Pre-asa Treatment Valuessupporting
confidence: 80%
See 2 more Smart Citations
“…Paradoxically, very high platelet counts can induce a bleeding tendency, mainly due to an acquired Von Willebrand's disease. 29 I fully agree with ELN recommendations that cytoreductive drugs in children with PV and ET should be prescribed as a last possibility and I suggest that, in the rare cases that need treatment, the selection of a cytotoxic or cytoreductive agent should be done after discussion with the child and parents. Hydroxyurea (HU) and interferon-alpha (IFN-a) are first line therapy at any age including children and young adults.…”
Section: How To Manage Childrenmentioning
confidence: 70%